Effect of MHD on Unsteady Flow with Fractional Maxwell Model - Nassief, Amaal Mohi (Al-Nahrain Journal of Science, 2018)
The aim of this paper is to study the effect of magnetic hydrodynamic (MHD) on unsteady flow of Maxwell fluid with fractional derivative due to a constant acceleration plate. The fractional calculus process is introduced to establish the constitutive relationship of fluid model, by using Laplace transform and Fourier sine transform, we obtained closed solutions for velocity field and shear stress. Lastly, the solutions are present by integral and series form in terms of the generalized G and R functions. The influence of the parameters on the velocity field spotlighted by means of the several graphs.